Spanish Wood Pasture: Origin and Durability of an Historical Wooded Landscape in Mediterranean Europe (Environment and History, 2008)
Spanish dehesas, the most extensive wood pastures in Mediterranean Europe, are a vivid example for demonstrating that the impact of rural communities on forests has not always been a bad thing. Environmental history is vital for understanding this cultural landscape. This article first analyses the origin of the dehesa. The border logic and the medieval Reconquest are elements that undoubtedly played a decisive part in its genesis; but, for the significance of Roman influence in Spain, it is necessary to consider the question of the possible existence of dehesas in Antiquity. The second aspect concerns the spreading of this landscape from the Middle Ages onwards. Dehesas are usually linked to the large properties owned by military orders, but most of all the spreading of the dehesa was favoured by the rise of transhumance from the thirteenth century onwards. Finally, the article emphasises that the durability of the Spanish wood pasture can be explained by a combination of several factors: insecurity along the border, the fact that transhumance was the most important industry in Spain for many centuries, and the protective laws adopted by the rural communities in order to protect their dehesas.

Spanish Wood Pasture: Origin and Durability of an Historical Wooded Landscape in Mediterranean Europe - Clément, Vincent (Environment and History, 2008)
Spanish dehesas, the most extensive wood pastures in Mediterranean Europe, are a vivid example for demonstrating that the impact of rural communities on forests has not always been a bad thing. Environmental history is vital for understanding this cultural landscape. This article first analyses the origin of the dehesa. The border logic and the medieval Reconquest are elements that undoubtedly played a decisive part in its genesis; but, for the significance of Roman influence in Spain, it is necessary to consider the question of the possible existence of dehesas in Antiquity. The second aspect concerns the spreading of this landscape from the Middle Ages onwards. Dehesas are usually linked to the large properties owned by military orders, but most of all the spreading of the dehesa was favoured by the rise of transhumance from the thirteenth century onwards. Finally, the article emphasises that the durability of the Spanish wood pasture can be explained by a combination of several factors: insecurity along the border, the fact that transhumance was the most important industry in Spain for many centuries, and the protective laws adopted by the rural communities in order to protect their dehesas.
Keywords: Dehesa; Mesta; Spanish Reconquest; Transhumance; woodland landscape